Unlocking Robertsonian translocated chromosomes in its repetitive DNA content to tackle genomic and mechanistic issues - Lopes, Mariana Faria (2019)
(Peri)centromeric repetitive sequences, and more specifically satellite DNA (SatDNA) sequences are a major heterochromatic genomic component, knowingly involved in Robertsonian translocations (ROBs). ROBs occur nonrandomly between acrocentric chromosomes (human chromosomes 13, 14, 15, 21 and 22). Presently, ROB mechanism and breakpoint location are still major issues, remaining not completely understood, essentially due to related assembly issues. The present work aims to inform about satellite arrangement (order and composition) in the context of the most common ROBs and, more precisely, Downassociated rob(14;21), by comparing up-to-date genome information and physical cytogenetic mapping with (peri)centromeric satellites (I, II, III, α and β). Between human classical satellites and in opposition to the greatly approached α satellite (αSat), satellite I (SatI) has been overlooked in respect to its presence, organization and significance. Thought to locate at the (peri)centromeric regions of chromosomes 3, 4 and acrocentric chromosomes, this satellite could be involved in the breakpoint of rob(14;21), being noteworthy for the context of ROB formation. In silico analysis in the framework of SatI is presented, along with physical mapping, allowing to identify assembly gaps related with this satellite: in silico mapping still did not correspond to physical mapping results. Accordingly, SatIshould be considered when addressing (peri)centromere-related ROBs, since the associated information gap is inevitable in the attempt to fully understand this rearrangement. In addition, (peri)centromeric SatDNAs were physically and in silico mapped, in order to analyze their presence and organization. Physical maps for chromosomes 14, 21 and der(14;21) allowed us to infer about the etiological and mechanistic origin of ROBs and the possible chain of events leading to this rearrangement. Physical mapping information was compared with in silico analysis, leading to the recognition of a substantial number of assembly gaps in the human reference genome. Therefore, it is possible to acknowledge the preserved utility of physically mapping satellite probes. Furthermore, the present work also demonstrates the uneven representation of satellite families in general comparatively to αSat (greatly represented in HSA14 and HSA21). The obtained results point out that the study of ROB mechanism and breakpoints still cannot exclusively rely on genomic technologies. Physical mapping should continue a prevailing player in the attempt to achieve accurate maps for pericentromeric/short-arm regions of acrocentric chromosomes. In order to entirely address these genomic regions with recent long- read technologies, sequential mapping steps must be followed. This work provides a clear mapping basis and, complementarily, a full gathering of current genomic data.